Josephine March’s Conflicts and Personalities Analysis in the Movie “Little Women (2019)” - Nada Sa’addiyah; Binti Qani’ah (MultiTech Publisher, 2024)
In this article, the focus was on the analysis of the conflict and personality of Josephine March the main character in the movie